1993
DOI: 10.1080/00224545.1993.9712116
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Interpersonal Relation Among Australian Children and Implications for Psychological Well-Being

Abstract: Three dimensions of interpersonal relations among Australian school children were hypothesized as reflecting tendencies (a) to bully others, (b) to be victimized by others, and (c) to relate to others in a prosocial and cooperative manner. School children from two secondary schools (School A, n = 285; School B, n = 877) answered 20 questions assessing styles of interpersonal relations. Factor analyses of the item scores obtained from each of the two schools provided highly similar results, supporting the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
257
1
20

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(297 citation statements)
references
References 6 publications
19
257
1
20
Order By: Relevance
“…Rational coping mechanisms may help prevent health-risk behaviors (Piko, 2001). effective management of interpersonal relationships is also preventive (Rigby & Slee, 1993). Previous research findings have provided evidence of the role of coping mechanisms in relation to adolescent health behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rational coping mechanisms may help prevent health-risk behaviors (Piko, 2001). effective management of interpersonal relationships is also preventive (Rigby & Slee, 1993). Previous research findings have provided evidence of the role of coping mechanisms in relation to adolescent health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we know that rational ways of coping may help prevent health-risk behaviors (Piko, 2001), and seeking harmony as a coping mechanism, in addition to helping to prevent substance use, has a beneficial influence on health-promoting behaviors (Piko & Keresztes, 2007). In addition, effective management of interpersonal relationships is also preventive (Rigby & Slee, 1993). Previous research results also draw attention to significant differences between high-and low-physical-activity groups of youth in relation to value orientation, life goals, and psychosocial health (Piko & Keresztes, 2006).…”
mentioning
confidence: 99%
“…Olweus (1989) argues that bullies have high self-esteem, while O'Moore and Hillery (1991) contended that bullies have a low sense of worth. In variance, Rigley and Slee (1993) found no relationship between bullying and self-esteem. Therefore, whether the tendency to bully others was associated with small self respect, has remained unresolved.…”
Section: Previous Researchmentioning
confidence: 77%
“…In the current study, the Cronbach alpha (Į) was 0.77. 4.2.3 Bullying was measured using the bully sub scale of the Peer Relationship Questionnaire (Rigley & Slee, 1993). The PRQ is a self-report questionnaire used to measure bullying, victimization and pro-social behavior among children between the ages of 12 to 18 years.…”
Section: Methodsmentioning
confidence: 99%
“…For the current study, bullies were identified using questions adapted and modified from Rigby and Slee's (1993) scoring of the Bullying Prevalence Questionnaire (BPQ) and from Rigby's (1997) Revised Pro-Victim Scale (RPVS) (Rigby & Slee, 1993). Bullies answered questions while together with the rest of the other students and their questionnaires were only isolated later, after the questionnaires had been collected.…”
Section: (De)limitationsmentioning
confidence: 99%